Pengaruh Buku Ajar IPA Terpadu Tema Kesehatan Pencernaan dalam Model Pembelajaran Kontekstual Adaptif Terhadap Kompetensi Siswa Kelas VIII SMPN 15 Padang - Rini Sarimayenti; Asrizal Asrizal; Yulkifli Yulkifli (PILLAR OF PHYSICS EDUCATION, 2018)
In 2013 curriculum, science teaching should be implemented in integrated  form in Junior High School. The real conditions show that integrated science teaching in school can’t implemented well. An alternative solution of this problem is to apply the integrated science textbook in adaptive contextual teaching model. The objective of this research was to investigate the effect of integrated science textbook on our digestive health theme in adaptive contextual teaching model toward the competences of the grade VIII students in  SMPN 15 Padang. The type of research was quasi experimental research with one group pretest-posttest design. Samples in this research were taken by using the purposive sampling technique. The research instruments consist of observation sheet for attitude competency, written test for knowledge competency and performance assessment for skill competency. Data of this research were analyzed by using descriptive statistical analysis and compare mean test for attitude, knowledge, and skill competences. The results of data analysis show that the implementation of integrated science textbook on our digestive health theme in adaptive contextual teaching model gives significant effect on the attitude, the knowledge and the skill competences at 95 % level confidence of grade VIII students in VIII SMPN 15 Padang.